Creep-Fatigue Behavior Evaluation by Reversible Permeability of CrMo Ferritic Steel for Ultra-Supercritical Steem Power Plants - Kim, C.S. (Проблемы прочности, 2016)
The creep-fatigue of ferritic CrMo steel has been investigated by measuring the peak interval of the reversible magnetic permeability profile. The peak interval of reversible permeability was discussed in relation to the microstructural evolution during creep-fatigue. The peak interval decreased monotonously during creep-fatigue to 0.8N f and increased thereafter. The decrease in the peak interval with increasing fatigue life fraction was related to the coarsening of fine precipitates and recovery of martensite laths. There is a strong linear relationship between the hardness and peak interval of reversible permeability.